A uniform code for the phenological stages of crops and weeds - Bleiholder, Hermann; Kirfel, Hanskarl; Langeluddeke, Peter; Stauss, Reinhold (Pesquisa Agropecuaria Brasileira, 1991)
The new BBCH code, in its general form, is a decimal system which makes possible the uniform coding of phenologically identical growth stages of all crops and weeds. The new code is based on the well known code for cereals developed by Zadoks et al. (1974), and avoids major changes from this widely used phenological key by utilizing similar principal and secondary groupings of growth stages. Although the code cannot describe every specific growth stage of all plant species in detail, the definitions and groupings employed are general enough to be universally utilized. In this way the BBCH code will contribute towards standardization and rationalization of data reporting in agricultural research and field testing. The applicability and practical benefits of the BBCH code will be demonstrated by the compilation and publication in the near future of growth stage for most major crops, as well as for representative categories of other plants.